Evaluatıon of Depressıon and Anxıety Status in Patıents After Cardıac Devıce Implantatıon - Murat Özmen; Onur Altunkaya; Selim Aydemir; Sidar Şiyar Aydın; Faruk Aydınyılmaz; Emrah Aksakal; Emre Alkan (Annals of Noninvasive Electrocardiology)
ABSTRACT Introduction Implantable cardioverter defibrillator (ICD) and pacemaker (PM) implantation may lead to anxiety and depression, which may reduce patients' quality of life. The aim of our study was to compare depression and anxiety following device implantation. Methods This prospective study was conducted on 202 patients admitted to our hospital with ICD and PM implants between January 2024 and January 2025. Results The prevalence of anxiety in PM and ICD recipients was 25.9% and 38.8%, respectively. There was a significant difference in anxiety in ICD patients (< 0.001). In terms of depression, the results in the PM and ICD groups were 18.9 and 38.9, respectively. The results showed a significant difference in the prevalence of depression between PM and ICD recipients. The tendency toward depression was statistically significant in both device recipients (PM; p = 0.008, ICD; p < 0.001). Conclusion Considering the prevalence of anxiety and depression, it seems necessary to pay closer attention to the anxiety and depression states of patients who have been treated with PM and ICD devices and to provide more widespread education to these patients.